2013
DOI: 10.1111/jsm.12023
|View full text |Cite
|
Sign up to set email alerts
|

SOP Conservative (Medical and Mechanical) Treatment of Erectile Dysfunction

Abstract: Introduction Erectile dysfunction (ED) is the most frequently treated male sexual dysfunction worldwide. ED is a chronic condition that exerts a negative impact on male self-esteem and nearly all life domains including interpersonal, family, and business relationships. Aim The aim of this study is to provide an updated overview on currently used and available conservative treatment options for ED with a special focus on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
130
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 177 publications
(311 reference statements)
1
130
0
9
Order By: Relevance
“…The treatment usually requires maximum doses of PDE5 inhibitors. In patients who do not respond to the first-line treatment or in case of whom such a treatment is contraindicated, it is possible to use prostaglandin administered into the urethra, injections to the cavernous bodies, vacuum devices or penile prostheses [4,5,14,15]. Currently, there are no studies confirming the higher efficacy and safety of any of the PDE5 inhibitors.…”
Section: Treatment Of Erectile Dysfunctions In Diabetic Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment usually requires maximum doses of PDE5 inhibitors. In patients who do not respond to the first-line treatment or in case of whom such a treatment is contraindicated, it is possible to use prostaglandin administered into the urethra, injections to the cavernous bodies, vacuum devices or penile prostheses [4,5,14,15]. Currently, there are no studies confirming the higher efficacy and safety of any of the PDE5 inhibitors.…”
Section: Treatment Of Erectile Dysfunctions In Diabetic Patientsmentioning
confidence: 99%
“…Treatment of erectile dysfunction is divided into three categories: oral phosphodiesterase type 5 inhibitors (PDE5i) constituting first-line treatment, alprostadil in injections to cavernous bodies and vacuums, which are the second choice options, as well as third-line treatment which encompasses the surgery with an implantation of penile prostheses of various kinds [2,5,6,8,14,15].…”
Section: Treatment Of Erectile Dysfunctions In Diabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead some to consider the possibility of suicide, because they consider ED a problem of their masculinity (Figueiredo & Schraiber, 2011). In addition to negatively affecting the individual's self-esteem, dysfunction can have serious consequences on other aspects of the subject such as anxiety and social isolation, as well as losses in interpersonal, family and work relationships (Porst et al, 2013;Phé & Rouprêt, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of PE and ED being very different conditions, with different characteristics and etiology, where ED is affected by lifestyle and clearly age-dependent [32] with a steep increase beyond the fifth decade [33][34][35][36] in our literature research we found several papers regarding personality traits and sexual dysfunctions in men, but few studies focused on personality traits and specific sexual dysfunctions like ED and PE (both lifelong and acquired), and on links between such personality traits and dysfunction severity.…”
Section: Introductionmentioning
confidence: 99%